Efektifitas Penerapan PP No.46 Tahun 2013 bagi UMKM terhadap Tingkat Pertumbuhan Wajib Pajak dan Penerimaan Pajak Penghasilan pada KPP Pratama di Semarang - Nirsetyo Wahdi; Suratman Suratman (Jurnal Ilmiah Aset, 2018)
Government, in order to facilitate and simplify taxation rules for UMKM, has issued Government Regulation No.46 of 2013, precisely valid starting from July 1, 2013. Tax in this Government Regulation is calculated from the turnover of each month by 1% and absolute. UMKM category is the taxpayer whose turnover or business circulation does not exceed 4.8 billion rupiahs per year. The purpose of this study is to determine the extent of the taxpayer growth and the income tax revenuefor eighteen months before and after the application of Government Regulation No.46 of 2013, in Tax ServiceOffice Pratama Semarang and UMKM which is benefited from the enactment of Government Regulation No. 46 of 2013. This studywas conducted by using descriptive method. The data used were secondary data obtained from several sources, the most important were derived from KPP Pratama Semarang. Data analysis used SPSS19. The results of the study show that there are significant differences towards the growth of the number of taxpayers and income tax revenue in KPP Pratama Semarang. After the application of Government Regulation No. 46 of 2013, the growth of the number of UMKM taxpayers increased in early 2014. The results show that the average amount of income tax revenue after the application of Government RegulationNo. 46 of 2013 is higher than the implementation of the regulation before. While UMKM which is benefited from the enactment of Government Regulation No. 46 of 2013, i.e the tax is imposed on the basis of 1% rate of turnover and absolute. If UMKMhas profit rate of more than 8%, soGovernment Regulation No. 46 of 2013 is more profitable because the tax paid is lower, compared to the rate of General Income Tax. But if the profit rate of UMKM is lower than 8%, the tax paid will be higher compared to the general rate. The tax amount will be the same either using rate ofGovernment RegulationNo. 46 of 2013 or the general rate when the profit rate is 8%. The newly established and unprofitable UMKM feels that the enactment of 1% tax from turnover through Government Regulation No.46 is unfair, because UMKM feel that they have not got the benefit but they have been taxed.